“Hal Pengabulan Doa” Kajian Hermeneutik Kritik Historis Matius 7:7-11 dan Implikasinya Bagi Jemaat GMIM Kanaan Winenet Wilayah Bitung XII - Sendow, Mieke N.; Mandagi, Thara I. K. (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2022)
in this study the author discusses the teaching of Jesus Christ on the Mount of Galilee in the New Testament Bible, known as the Sermon on the Mount, especially in Matthew 7:7-11 regarding, the answering of Prayers, which is how as persons Christian (People who believe in Jesus Christ) who always relies on God in every aspect of the journey of life by asking for His guidance, in life through prayer delivered and prayers delivered, will be granted. this ressearch uses Historical Criticism approach was used to explore the text as well as observations and interviews to find out the reality on the ground and obtain the maximum interpretation and the right theology. So that with the answered prayer, it can make the GMIM Canaan Winenet Congregation of Bitung XII Region, always continue to pray diligently, seek God in any situation and condition and continue to strive for what is prayed for or conveyed to God while maintaining a life that is pleasing to God, even though not all prayers delivered will be answered but with faith believing that God will give, what is best for His people and He will never to leave His people under any circumstances.